Young parents' experiences and perceptions of 'Teen Mom' reality shows. (14th September 2019) - Greyson, Devon; Chabot, Cathy; Shoveller, Jean A.
ABSTRACT: MTV's hit reality shows 16 and Pregnant and Teen Mom were produced with an agenda of preventing teen pregnancy. Researchers have examined their effectiveness as behavioral interventions, yet little attention has been paid to experiences of young parents themselves with these shows, nor to their ethical consequences, including the potential for compounding of stigma against young parents. This analysis qualitatively examines the experiences of young parents in British Columbia, Canada, with the media phenomenon referred to as 'Teen Mom shows.' Interview and observation data from a large, longitudinal, mixed-methods ethnographic study of young parents was analyzed using hybrid deductive-inductive qualitative content analysis. The dominant understanding was that Teen Mom depictions of young parenting were inaccurate and overly dramatic. Young mothers and fathers experienced stigma and judgement that directly or indirectly referred to Teen Mom portrayals of young mothers as immature, dramatic, and promiscuous, and young fathers as absentee parents.